Penerapan Metode GRA-DEMATEL Pada Pilihan E-Commerce Fashion Gen Z - Rini Kurniasih; Didi Suhaedi; Erwin Harahap (Jurnal Riset Matematika, 2025)
Abstract. The rapid growth of fashion e-commerce has encouraged Generation Z, as digital natives, to navigate various online shopping platforms. Their unique consumption preferences, shaped by impulsive lifestyles and high exposure to social media, present challenges in selecting the most suitable e-commerce platform for fashion purchases. This study aims to determine the best e-commerce platform for Gen Z in fashion shopping using a Multi-Criteria Decision Making (MCDM) approach. This quantitative research involved 111 Gen Z respondents residing in the Greater Bandung area who have shopped for fashion products on Shopee, Tokopedia, and Lazada. Data were collected through an online questionnaire and processed using the Entropy method to objectively weigh the evaluation criteria, Grey Relational Analysis (GRA) to rank the alternatives, and the Decision Making Trial and Evaluation Laboratory (DEMATEL) to analyze the interrelationships among criteria. The evaluation was based on four main criteria: price, product, appeal, and user experience. The results indicate that Shopee ranks first as the preferred platform. The DEMATEL analysis identified product and price as the most influential criteria affecting appeal and user experience. These findings contribute to a better understanding of Gen Z’s shopping behavior and offer strategic insights for e-commerce platforms seeking to enhance competitiveness and user satisfaction. Abstrak. Pertumbuhan e-commerce fashion yang pesat mendorong Gen Z, sebagai generasi digital native, untuk menghadapi berbagai pilihan platform belanja daring. Preferensi konsumsi mereka yang unik, dipengaruhi gaya hidup impulsif dan eksposur media sosial, menimbulkan tantangan dalam memilih platform e-commerce yang paling sesuai. Penelitian ini bertujuan menentukan platform e-commerce terbaik bagi Gen Z dalam pembelian produk fashion dengan pendekatan Multi-Criteria Decision Making (MCDM). Penelitian bersifat kuantitatif dengan melibatkan 111 responden Gen Z yang berdomisili di wilayah Bandung Raya dan pernah berbelanja fashion di Shopee, Tokopedia, dan Lazada. Data dikumpulkan melalui penyebaran kuesioner daring, kemudian diolah menggunakan metode Entropy untuk pembobotan kriteria secara objektif, Grey Relational Analysis (GRA) untuk pemeringkatan alternatif, serta Decision Making Trial and Evaluation Laboratory (DEMATEL) untuk menganalisis hubungan antarkriteria. Evaluasi dilakukan berdasarkan empat kriteria: harga, produk, daya tarik, dan pengalaman pengguna. Hasil menunjukkan bahwa Shopee menempati peringkat pertama sebagai platform pilihan. Analisis DEMATEL mengidentifikasi produk dan harga sebagai kriteria paling berpengaruh terhadap daya tarik dan pengalaman pengguna. Temuan ini memberikan kontribusi dalam memahami perilaku belanja Gen Z serta menjadi referensi bagi pelaku e-commerce dalam merancang strategi yang relevan dan kompetitif.